2019
DOI: 10.3389/fendo.2019.00870
|View full text |Cite
|
Sign up to set email alerts
|

Decreases in Circulating Concentrations of Long-Chain Acylcarnitines and Free Fatty Acids During the Glucose Tolerance Test Represent Tissue-Specific Insulin Sensitivity

Abstract: Background: Insulin plays a pivotal role in the regulation of both carbohydrate and lipid intermediate turnover and metabolism. In the transition from a fasted to fed state, insulin action inhibits lipolysis in adipocytes, and acylcarnitine synthesis in the muscles and heart. The aim of this study was to measure free fatty acid (FFA) and acylcarnitine levels during the glucose tolerance test as indicators of tissue-specific insulin resistance. Results: Insulin release in response to glucose administration decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Also, AOS helped protect β cells from death and degeneration, suggesting that AOS treatment can decrease the apoptosis of pancreatic cells and alleviate IR. Moreover, many animal and human studies have demonstrated that FFAs are key factors responsible for IR ( Boden 2003 ; Makarova et al, 2019 ; Qureshi et al, 2019 ). Excessive blood FFA levels can cause IR in peripheral tissues by suppressing muscle glucose uptake and glycogen synthesis and cause β-cell dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Also, AOS helped protect β cells from death and degeneration, suggesting that AOS treatment can decrease the apoptosis of pancreatic cells and alleviate IR. Moreover, many animal and human studies have demonstrated that FFAs are key factors responsible for IR ( Boden 2003 ; Makarova et al, 2019 ; Qureshi et al, 2019 ). Excessive blood FFA levels can cause IR in peripheral tissues by suppressing muscle glucose uptake and glycogen synthesis and cause β-cell dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Although dosing according to lean mass has been suggested by some studies especially when body composition is relatively similar, a larger body of literature argues against that because non-lean tissue mass like the white and brown fat and the brain can significantly contribute to whole-body glucose uptake 27 29 . This is particularly important in obese animals, in which the non-lean mass can make up to 50% of the body weight, and relative to the muscles, adipose glucose uptake is as high as 30% in obese mice 28 . Thus, total body weight has been adapted for glucose/insulin tolerance tests and normalization of EE data in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The role of these interactions has become particularly relevant for understanding the mechanisms underlying insulin resistance, which precedes the onset of type 2 diabetes. An elevated LCAC content is associated with impaired insulin sensitivity in patients [ 15 ], and this association has been further characterized in animal models of insulin resistance [ 45 , 46 ]. Our present data highlight a role for LCAC in the regulation of the molecular mechanisms of insulin signalling and explain the aspects of insulin resistance and hyperinsulinaemia, which are associated with type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%